Data For The Project Investigating Movement Of Terrestrial Rodents In Riparian Reserves - Gutierrez Al-Khudhairy, Selene; Ewers, Robert M. (Zenodo, 2018)
Description: The spool-and-line technique was used to observe the efficacy with which small mammals are able to use riparian strips as dispersal corridors within a fragmented landscape. I set up transects along established riparian strips in mature oil palm plantations, using novel sites >1000m away from existing SAFE project sites to avoid conflict with other projects. These included riparian strips of widths ranging from 10-120 metres. Control (continuous twice-logged forest) sites will be set up within the SAFE landscape. For each riparian transect, I set twenty Tomahawk-style steel cage traps baited with oil palm fruit at 15m intervals along the transect, with a constant distance from the oil palm edge of the riparian zone. To avoid physiological stress to the mammals, traps were set up only in well-shaded microhabitats in dense cover, with sufficiently large and fresh bait to provide adequate nutrition. I checked trapping transects everyday and re-set each day at dusk. This study will focus on common and resilient rats of the genus Maxomys. I only focus on adults and subadults, and released vulnerable juveniles and pregnant females released. Animals caught were identified, sexed and aged, and either released or retained for tracking, depending on several criteria. Spooled individuals will fit weight criteria such that any attached spool device does not exceed 5% of the individual's body weight. Animals over 40g were tracked with a small spool (length=88m), while animals over 100g will use a large spool (length=220m). Animals below the 40g cut-off were released. This ensures representative movement is observed, and meets widely-accepted ethical guidelines for tracking devices. Animals fitted with a spooling device were firstly anaesthetised with diethyl ether to obtain biometric measurements (hind foot, ano-genital distance and weight), the sex, age and species for each individual. As well as providing back-up information in the case of uncertain ID, these data are important covariates of observed movement behaviour. To track the movement path of selected individuals, I attached a temporary lightweight bobbin of thread to the animal. A hair clip will be taken from the upper back region to provide a fur-based attachment point for the spool using cyanoacrylate gel glue. To spool package was a bobbin double-wrapped in a cling-film layer that allows smooth unravelling, and then wound in a gaffer tape layer that avoids snagging on foliage. The total weight of the package did not exceed 5% of the average minimum weight of each species. Once processed, I translocated individuals from their site of capture by ~50m to a release site longitudinally along the same riparian reserve. The proximal end of the thread was tied to a fixed or heavy structure such as the trap so that as the animal is released from the trap, the freely unravelling thread catches onto vegetation and topography, revealing the movement patterns of the individual. Movement paths were divided into steps, with a step being defined as a length of the animal's track where it does not deviate from a straight line by more than 10 degrees. I measured the length of steps and the angles between them using a tape measure and compass to construct a detailed two-dimensional map of each animal's route through space. From this, I obtained a measure of path tortuosity (fractal dimension and deviation from a correlated random walk) for each tracked movement path. Project: This dataset was collected as part of the following SAFE research project: Determining the importance of riparian reserves to maintain the dispersal of small mammals in a fragmented landscape in Sabah, Malaysia XML metadata: GEMINI compliant metadata for this dataset is available here Data worksheets: There are 2 data worksheets in this dataset: Data collected from spool-and-line tracking of terrestrial rodents (Worksheet SpoolData)Dimensions: 5544 rows by 14 columnsDescription: This worksheet contains the data I collected from the spool-and-line tracking. Each tracked rodent individual has a corresponding unique identification number, given by the name in the 'Path_code' column. The 'Path_code' identification number of a tracked individual corresponds to the same individual in the 'Trapping and Fractal data' worksheet. The 'Step_number' column indicates the order of individual steps of a movement path for a tracked rodent. The direction bearing of an individual movement path step is presented in the 'Step_bearing' column. The 'Step_length' column contains the length in centimeters of an individual movement step. The 'Matrix' coloumn indicates whether the rodent was released in a riparian reserve (RR) or continuous twice-logged forest (CF) habitat.Fields: Transect_location : Location of the transect (Field type: Location) Date_trap : Date traps were set (Field type: Date) Date_release : Date individuals were released (Field type: Date) Date_spool : Date a spool path was recorded (Field type: Date) Site_id : Transect ID (Field type: ID) Trap_number : Location of trap along the transect (Field type: Numeric) Release_location : Grid coordinates for location where a spooled individual was released (Field type: ID) Species : Species (Field type: Taxa) Path_code : Unique spool path ID (Field type: ID) Step_number : The sequential order of the movement steps of a spool path (Field type: Numeric) Step_bearing : Movement step bearing (Field type: Numeric) Step_length : Movement step length (Field type: Numeric) Matrix : Habitat adjacent to riparian forest (Field type: Categorical) Rodent trapping and fractal analysis data (Worksheet TrappingData)Dimensions: 1102 rows by 40 columnsDescription: This worksheet contains data from rodent surveys I conducted in riparian reserves and continuous twice-logged forest habitats. It contains morphometric data of individuals, including: weight (g), hind foot (cm) and AGD (cm). As well as the species (Maxomys whiteheadi/MW, Maxomys surifer/MS, Maxomys rajah/MR, Niviventer cremoriventer/DTT, Sundamys muelleri/MR, Rattus norvegicus/BR or Leopoldamys sabanus/LTG), sex (Female/F and Male/M) and age (Adult/A, Subadult/SA or Juvenile/J) of individuals. The coloumn 'Entered_op' contains data on whether an individual crossed over from the riparian corridor habitat into the adjacent oil palm (1 = entered oil palm habitat). It also contains the data output of the fractal analysis (fractal dimension/D_dimension and correlated random walk/CRW_Diff) of the movement trajectories. Fields: Transect_location : Location of the transect (Field type: Location) Date_trap : Date traps were set (Field type: Date) Date_process : Date the individual was processed or attached with a spooling devie (Field type: Date) Date_release : Date individuals were released (Field type: Date) Date_spool : Date a spool path was recorded (Field type: Date) Site_id : Transect ID (Field type: ID) Trap_Location : Grid coordinate of the trap (Field type: ID) Trap_number : Location of trap along the transect (Field type: Numeric) Trap_success : Whether an individual was trapped (Field type: Categorical) Death : Recorded deaths (Field type: Categorical) Process_time : Time at which an animal was spooled and released (Field type: Time) Release_distance : Distance or grid coordinates along the transect where a spooled individual was released (Field type: ID) Release_location : Site of release within the riparian corridor (Field type: Categorical) Release_distance_from_edge : Distance from oil palm edge where an individual is released in a riparian reserve (Field type: Numeric) SF_release : Whether a spool fell immediately upon release (Field type: Categorical) Species : Species (Field type: Taxa) Sex : Sex of individual (Field type: Categorical) Age : Age of individual (Field type: Categorical) Weight : Weight of individual (Field type: Numeric) Hind_foot : Length of hind foot of an individual (Field type: Numeric) AGD : Anogenital distance of individual (Field type: Numeric) Ear : Length of ear (Field type: Numeric) Path_code : Unique spool path ID (Field type: ID) Spool_follower : Person who tracked the spool path (Field type: Comments) Matrix : Habitat adjacent to trapping grid (Field type: Categorical) Distance_translocated : Distance an individual was translocated from its capture point (Field type: Numeric) Path_end : Reason why spool fell off (Field type: Categorical) Spool_totalsteps : Total number of movement path steps in the tracked spool path (Field type: Numeric) Spool_totallength : Total length of a spool path (Field type: Numeric) Dist_from_release : Distance from the spool path end to the release site (Field type: Numeric) Entered_op : Whether the tracked individual crossed over from the riparian reserve into the oil palm habitat (Field type: Categorical) D_dimension : Fractal Dimension of the movement path (Field type: Numeric) Total_steps : The sum of steps in an individual's movement path (Field type: Numeric) Total_length : Total length of the tracked movement path (Field type: Numeric) Min_stepsize : The shortest movement path step taken (Field type: Numeric) Max_stepsize : The longest movement path step taken (Field type: Numeric) Mean_stepsize : The mean step length of a movement path (Field type: Numeric) CRW_Diff : Deviation of movement path from a correlated random walk (Field type: Numeric) Rainfall : If it was raining when the spooled individual was released (Field type: Ordered Categorical) Date range: 2016-03-07 to 2016-06-25 Latitudinal extent: 4.6505 to 4.7255 Longitudinal extent: 117.4532 to 117.6286 Taxonomic coverage: All taxon names are validated against the GBIF backbone taxonomy. If a dataset uses a synonym, the accepted usage is shown followed by the dataset usage in brackets. Taxa that cannot be validated, including new species and other unknown taxa, morphospecies, functional groups and taxonomic levels not used in the GBIF backbone are shown in square brackets.Animalia - Chordata - - Mammalia - - - Rodentia - - - - Muridae - - - - - Chrotomys - - - - - - Chrotomys whiteheadi (as Maxomys whiteheadi ) - - - - - Leopoldamys - - - - - - Leopoldamys sabanus - - - - - Maxomys - - - - - - Maxomys rajah - - - - - - Maxomys surifer - - - - - Niviventer - - - - - - Niviventer cremoriventer - - - - - Rattus - - - - - - Rattus exulans - - - - - - Rattus norvegicus - - - - - Sundamys - - - - - - Sundamys muelleri